Gamma-irradiated β-glucan modulates signaling molecular targets of hepatocellular carcinoma in rats - Sawsan M Elsonbaty; Walid E Zahran; Fatma SM Moawed (Tumor Biology)
β-glucans are one of the most abundant forms of polysaccharides known as biological response modifiers which influence host’s biological response and stimulate immune system. Accordingly, this study was initiated to evaluate irradiated β-glucan as a modulator for cellular signaling growth factors involved in the pathogenesis of hepatocellular carcinoma in rats. Hepatocellular carcinoma was induced with 20 mg diethylnitrosamine/kg BW. Rats received daily by gastric gavage 65 mg irradiated β-glucan/kg BW. It was found that treatment of rats with diethylnitrosamine induced hepatic injury and caused significant increase in liver injury markers with a concomitant significant increase in both hepatic oxidative and inflammatory indices: alpha-fetoprotein, interferon gamma, and interleukin 6 in comparison with normal and irradiated β-glucan–treated groups. Western immunoblotting showed a significant increase in the signaling growth factors: extracellular signal–regulated kinase 1 and phosphoinositide 3-kinase proteins in a diethylnitrosamine-treated group while both preventive and therapeutic irradiated β-glucan treatments recorded significant improvement versus diethylnitrosamine group via the modulation of growth factors that encounters hepatic toxicity. The transcript levels of vascular endothelial growth factor A and inducible nitric oxide synthase genes were significantly higher in the diethylnitrosamine-treated group in comparison with controls. Preventive and therapeutic treatments with irradiated β-glucan demonstrated that the transcript level of these genes was significantly decreased which demonstrates the protective effect of β-glucan. Histological investigations revealed that diethylnitrosamine treatment affects the hepatic architecture throughout the significant severe appearance of inflammatory cell infiltration in the portal area and congestion in the portal vein in association with severe degeneration and dysplasia in hepatocytes all over hepatic parenchyma. The severity of hepatic architecture changes was significantly decreased with both β-glucan therapeutic and preventive treatments. In conclusion, irradiated β-glucan modulated signal growth factors, vascular endothelial growth factor A, extracellular signal–regulated kinase 1, and phosphatidylinositol-3-kinase, which contributed to experimental hepatocarcinogenesis.